Pentingnya Mengembangkan Bakat Akademik Khusus Remaja Melalui Komunikasi Interpersonal yang Efektif - Iva Madelyn Hasugian; Ali Ardiansyah; Annisa Wahyuni Arsyad (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Each individual is born with diverse talents. One of the types of self-talent is the specific academic talent that potentially benefits for children's future. In this case, effective interpersonal communication between parents and children may influence the process of exploring and developing specific academic talents. This study aims to describe influential factors in the development of special self-talent and analyze how interpersonal communication can be used to assist the process. Accordingly, qualitative research conducted using observation, interviews, and documentation. This study interviewed 4 students with high achieving scores in the specific academic subject and their parent, as well as 1 teacher of supervising coordinator in SMA Negeri 3 Samarinda. The results show that effective interpersonal communication between parents and children played an important role to help the development of adolescent talents.